Study of Different Treatment Methods on Chicken Feather Biomass - Swati, Sharma; Gupta, Arun; Syed Mohd Saufi, Tuan Chik; Chua, Gek Kee; Praddep, Kumar Podder; Malini, Subramaniam; Jayshree, Thraisingam (IIUM, 2017)
The chicken feathers (CFs) consist of up to 10 % of total chicken dry mass and they have many potential industrial applications. CFs contains protein fibers named as keratin, which is an insoluble protein. Primary sanitization phases are complex because of the presence of lots of blood born microbes, pathogens and parasites in raw biomass. The extraction process of keratins from the unprocessed feathers is also a challenging task. Prior to the extraction cleaning/sanitization of feathers is a very necessary step. Thus, the present work was conducted to optimize an efficient surfactant for the cleaning process of the CFs by using ionic and non-ionic surfactants. The experiment was conducted by the washing of feathers with double distilled water (ddH2O), detergents, ether and lastly with boiling water. The washed feathers treated with surfactants and the effect of each surfactant was analyzed by a microbiological test which tells about the extent of the presence of different bacteria on the treated feathers. SEM, EDX, FTIR were used to study the morphology and composition of untreated and treated CFs. SEM showed there was no detectable fiber damage after treatment. Cetrimonium bromide (CTAB) (t3) was one of the best surfactant for the treatment of CFs among all the surfactant used. The present study described the best treatment method for the CFs.